Comparison of the health related physical fitness of adults of differents ages - Douglas Fernando Dias; Isabel Cristina Brisotti dos Reis; David Augusto dos Reis; Edilson Serpeloni Cyrino; David Ohara; Ferdinando Oliveira Carvalho; Juliano Casonatto; Mathias Roberto Loch (Universidade Federal de Santa Catarina, 2008)
http://dx.doi.org/10.5007/1980-0037.2008v10n2p123 The objective of this study was to investigate possible differences in the levels of health related physical fitness of men and women of different ages. The sample comprised 326 people (132 men and 194 women) who did not perform regular physical exercise, and who were separated for analysis by sex and into three age groups: 20-29 years (G1), 30-39 years (G2) and 40-49 years (G3). All subjects underwent anthropometric measurements and motor performance testing (flexibility, muscle resistance/strength and cardiorespiratory fitness). Statistical analysis employed the Levene test to verify the homogeneity of variation, descriptive statistics, single factor ANOVA (age group) and the Bonferroni test. The significance level adopted was p<0.05. The best levels of physical fitness were observed among the youngest subjects (G1), irrespective of sex, while the worst fitness levels were detected in the oldest subjects (G3). The variation in body fat from G1 to G3 was more accentuated among the men (34%) than among the women (16%). With relation to motor performance, the greatest percentage differences between G1 and G3 were detected by either modified abdominal test (39%and 22%, for men and women respectively) and the arm flexion and extension test(31% and 24%, for men and women respectively. The results suggest that among individuals who do not regularly practice physical exercise there is a natural tendency for health related physical fitness to reduce as age increases.